2011
DOI: 10.1182/blood-2010-05-284513
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase attracts neutrophils by physical forces

Abstract: Recruitment of polymorphonuclear neutrophils (PMNs) remains a paramount prerequisite in innate immune defense and a critical cofounder in inflammatory vascular disease. Neutrophil recruitment comprises a cascade of concerted events allowing for capture, adhesion and extravasation of the leukocyte. Whereas PMN rolling, binding, and diapedesis are well characterized, receptor-mediated processes, mechanisms attenuating the electrostatic repulsion between the negatively charged glycocalyx of leukocyte and endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
105
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 44 publications
9
105
1
5
Order By: Relevance
“…MPO appears to be involved in positive feedback regulation of inflammation, as observed in both published literature (43)(44)(45)(46)(47) and our study. Indeed, investigators in a recent study found that MPO can bring together endothelial and leukocyte membranes via electrostatic forces (44), potentially acting as a positive feedback for cell recruitment.…”
Section: Molecular Imaging: Myeloperoxidase As Therapeutic Target Forsupporting
confidence: 66%
See 1 more Smart Citation
“…MPO appears to be involved in positive feedback regulation of inflammation, as observed in both published literature (43)(44)(45)(46)(47) and our study. Indeed, investigators in a recent study found that MPO can bring together endothelial and leukocyte membranes via electrostatic forces (44), potentially acting as a positive feedback for cell recruitment.…”
Section: Molecular Imaging: Myeloperoxidase As Therapeutic Target Forsupporting
confidence: 66%
“…Indeed, investigators in a recent study found that MPO can bring together endothelial and leukocyte membranes via electrostatic forces (44), potentially acting as a positive feedback for cell recruitment. This is consistent with our observation of decreased inflammatory cell infiltration of the brain after MPO inhibition.…”
Section: Molecular Imaging: Myeloperoxidase As Therapeutic Target Formentioning
confidence: 99%
“…Klinke et al demonstrate that the proinflammatory actions of MPO may extend to promotion of leukocyte recruitment. 5 MPO is shown to invoke directional neutrophil movement in in vitro chemotaxis experiments, independent of its enzymatic activity and intracellular processes in neutrophils such as phosphatidylinositol 3-kinase activity and actin polymerization. Most interestingly, even fixed/dead neutrophils were attracted toward MPO, as were negatively charged beads.…”
mentioning
confidence: 97%
“…In this issue, Klinke et al demonstrate that the highly cationic MPO molecule is able to attract leukocytes via its electrostatic characteristics. 5 MPO is a heme-containing peroxidase highly expressed by polymorphonuclear neutrophils. Its major function is generation of hypochlorous acid as part of the neutrophil's antimicrobial armory.…”
mentioning
confidence: 99%
“…First, we investigated the contribution of neutrophil-related enzymes such as MPO or ELANE for EAE development. MPO is involved in the regulation of endothelial barrier permeability (21) and the transmigration of neutrophils to inflamed sites (22). ELANE, together with proteinase 3, has been described to generate a proinflammatory environment by degrading anti-inflammatory progranulin, thereby producing proinflammatory granulin peptides (23).…”
Section: Cns-infiltrating Neutrophils Are a Source Of Cytokinesmentioning
confidence: 99%